1999
DOI: 10.1128/mmbr.63.3.523-553.1999
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of O-Antigen Biosynthesis inPseudomonas aeruginosa

Abstract: SUMMARY Pathogenic bacteria produce an elaborate assortment of extracellular and cell-associated bacterial products that enable colonization and establishment of infection within a host. Lipopolysaccharide (LPS) molecules are cell surface factors that are typically known for their protective role against serum-mediated lysis and their endotoxic properties. The most heterogeneous portion of LPS is the O antigen or O polysaccharide, and it is this region which confers serum resistance to the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
223
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(229 citation statements)
references
References 231 publications
(378 reference statements)
3
223
0
Order By: Relevance
“…In addition, the lack of Psl in the algC mutant was not due to the LPS defect. Taken together, our data revealed that AlgC was required for the biosynthesis of Psl, likely due to the role of AlgC in generating the precursors as it does in the biosynthesis pathway of alginate and LPS (Coyne et al, 1994;Deretic et al, 1995;Rocchetta et al, 1999).…”
Section: Algc Is Required For the Synthesis Of Psl Exopolysaccharidementioning
confidence: 62%
See 1 more Smart Citation
“…In addition, the lack of Psl in the algC mutant was not due to the LPS defect. Taken together, our data revealed that AlgC was required for the biosynthesis of Psl, likely due to the role of AlgC in generating the precursors as it does in the biosynthesis pathway of alginate and LPS (Coyne et al, 1994;Deretic et al, 1995;Rocchetta et al, 1999).…”
Section: Algc Is Required For the Synthesis Of Psl Exopolysaccharidementioning
confidence: 62%
“…The control of the surface polysaccharide synthesis is a critical bacterial survival in the environment and human host (Rocchetta et al, 1999;Hall-Stoodley et al, 2004;Ramsey and Wozniak, 2005;Danhorn and Fuqua, 2007;Hoiby et al, 2010). Pseudomonas aeruginosa can produce several exopolysaccharides; each has distinct roles in biofilm development (Ghafoor et al, 2011;Yang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The genetics of the O-chain biosynthesis in P. aeruginosa has been extensively characterized and reviewed by Rocchetta et al [32]. The genes encoding the glycosyl transferases for the transfer of the sugar residues of the O-antigen units of serotype O5 and O6 have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Although significant progress has been made in identifying genes involved in LPS synthesis in P. aeruginosa [8][9][10][11][12], the genetic changes leading to stable acquisition of the LPS rough phenotype have not yet been correlated with the chemical changes that occur in the LPS of cystic fibrosis isolates. Core structures for P. aeruginosa serogroups O2, O3, O5 and O6 and derived mutant strains have been reported [13][14][15][16][17][18][19][20].…”
mentioning
confidence: 99%